Epidemiological and Clinical Aspects of Neonatal Dermatoses at the National Teaching Hospital HKM of Cotonou Benin - ADEGBIDI, HUGUES DANIEL GBADEBO (My University, 2017)
Neonatal dermatoses (NND) are frequent, varied and of variable prognosis. The objective of this work was to study the epidemiological and clinical aspects of NND at the NTH-HKM. Methods: This was a cross-sectional descriptive and analytical study from December 1, 2014 to February 28, 2015. All newborns received in the Department of Pediatrics and Medical Genetics and with dermatosis were included. The diagnosis of dermatoses was clinical. Results: During the study period, 355 newborns had at least one NND on a total of 580 newborns received, a prevalence of 61.2%. The sex ratio was 1.54 and the average age was 3.11 days. Transient dermatoses were more frequent (80%), dominated by desquamation + xerosis (33.75%). Congenital melanocytic nevi (40.74%) and malformations and vascular tumors (18.52%) were the most noted pathological neonatal dermatoses. Only age was statistically associated with NND. Conclusion: DNH is common in newborns at the NTH-HKM. They were mostly transitory. Pathological conditions should be treated where appropriate.
Keywords: Epidemiological and Clinical Aspects; Dermatoses; Newborns; Benin